Differences in Symptom Severity and Quality of Life among Patients with Cancer Using Conventional Therapies with/ without Herbal Medicines in Uganda: A Cross-Sectional Study - Asiimwe, John Baptist; Nagendrappa, Prakash B.; Jatho, Alfred; Kamatenesi, Maud M.; Atukunda, Esther C. (Asian Pacific Journal of Cancer Prevention, 2023)
Objective: Patients with cancer experience numerous symptoms related to cancer and treatment side effects that reduce their quality of life (QOL). Although herbal medicine (HM) is used to manage such symptoms by patients in sub-Saharan Africa, data on patients’ perceived clinical outcomes are limited. We compared differences in QOL and symptom severity between patients with cancer using HM plus conventional therapies (i.e., chemotherapy, hormonal therapy, radiotherapy, surgery) and those using conventional therapies alone. Methods: This cross-sectional study included patients with cancer aged >18 years who were consecutively sampled and completed a researcher-administered questionnaire between December 2022 and January 2023. Specifically, data was collected using The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and the MD Anderson Symptom Inventory for Traditional Chinese Medicine (MDASI-TCM). Data were analyzed using descriptive statistics and chi-square and logistic regression analyses. Results: Of 400 participants (67.5% female), 49% (n=195) used HM plus conventional therapies and 51% (n=205) used conventional therapies alone. Most participants were aged >38 years (73.3%; median age 47 years). A univariate analysis showed the HM plus conventional therapies group had better mean scores for most QOL and symptom severity measures than the conventional therapies alone group. However, only role functioning significantly differed (p=0.046) in the bivariate analysis. There were no statistically significant differences between the two groups after confounder adjustment for all others measures of symptom severity and QOL. Conclusion: HM plus conventional therapies may offer minimal benefits or differences for clinical outcomes among patients with cancer. However, our findings have clinical, research, and public health implications for Uganda and other sub-Saharan African settings.
Keywords: Quality of life; Symptom severity; Oncology; Herbal medicine; Patients